THE EFFECT OF ADDING BLACK SOLDIER FLY (Hermetia illucens) MAGGOT FLOUR IN THE RATION ON THE DIGESTIVE SYSTEM OF BROILERS - I P. I., Pratama; Sudiastra, I W.; Suarta, G. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
This research aims to determine the effect of giving maggot flour on the broiler digestive system. This research was conducted in Tengkudak Village, Penebel District, Tabanan Regency, Bali and lasted for four weeks, namely from April-May 2023 using a 547 completely randomized design consisting of four treatments and four replications where each replication consisted of four broilers. Treatment consisted of P0 (without maggot flour supplementation), P1 (ration with 3% maggot flour supplementation), P2 (ration with 6% maggot flour supplementation), P3 (ration with 9% maggot flour supplementation). The variables observed were the percentage of heart, liver, pancreas, spleen, proventriculus, ventriculus, bile, small intestine, cecum and large intestine. The results of this study showed that the percentage of heart, pancreas and cecum in treatments P1, P2 and P3 was significantly different (P<0.05) compared to treatment P0, then the percentage of weight of liver, spleen, proventriculus, ventriculus, bile, small intestine, and large intestine produced no significant differences (P>0.05) compared to P0 treatment. The results of this study can be concluded that the addition of 3%, 6%, and 9% maggot flour to commercial rations reduces the percentage of heart, pancreas, and cecum, but gives the same results on the percentage of weight of liver, spleen, ventricle, proventriculus, bile, and small intestine, and large intestine.